2016
DOI: 10.1080/1756073x.2016.1221638
|View full text |Cite
|
Sign up to set email alerts
|

Sport, Chaplaincy and Holistic Support: The Elite Player Performance Plan (EPPP) in English Professional Football

Abstract: The University of Gloucestershire accepts no liability for any infringement of intellectual property rights in any material deposited but will remove such material from public view pending investigation in the event of an allegation of any such infringement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 16 publications
4
33
0
Order By: Relevance
“…In this role, chaplains offer practical, spiritual and pastoral support, as well as providing assistance with wider lifestyle issues (Gamble et al 2013;Nesti and Sulley 2015). At times, players and staff may be reticent to engage with such support on account of the mistaken perception that the chaplain is there to proselytise their faith and research suggests that club managers may be influential in this respect (Roe and Parker 2016). In their study of the relationship between sports chaplains and sport psychologists in the English Premier League, Gamble et al (2013) found that chaplains felt that their role may be either empowered or disempowered depending on the attitude of a team manager towards them.…”
Section: Chaplaincy and Uk Sportmentioning
confidence: 99%
See 4 more Smart Citations
“…In this role, chaplains offer practical, spiritual and pastoral support, as well as providing assistance with wider lifestyle issues (Gamble et al 2013;Nesti and Sulley 2015). At times, players and staff may be reticent to engage with such support on account of the mistaken perception that the chaplain is there to proselytise their faith and research suggests that club managers may be influential in this respect (Roe and Parker 2016). In their study of the relationship between sports chaplains and sport psychologists in the English Premier League, Gamble et al (2013) found that chaplains felt that their role may be either empowered or disempowered depending on the attitude of a team manager towards them.…”
Section: Chaplaincy and Uk Sportmentioning
confidence: 99%
“…One of the ways in which this often plays out within the context of English professional football is via the neutrality and independence of the chaplain's position in relation to club hierarchies and decision making processes (Weir 2016). Unlike other support services, chaplains are not typically employed by the clubs that they serve and do not therefore report directly to management on matters of welfare or performance (Roe and Parker 2016). Professional footballers can be reluctant to speak to those with decision-making responsibilities (i.e., club management and coaching staff) about personal issues due to the impact that this may have on team selection and/or career progression (Nesti and Sulley 2015).…”
Section: Chaplaincy and Uk Sportmentioning
confidence: 99%
See 3 more Smart Citations